Fragmented patch patterns accelerate evapotranspiration: Implications for alpine meadow restoration - Wei Zhang; Jinglin Zhang (Ecological Indicators, 2025)
Landscape patch patterns are extensively used to reflect the functions and states of ecosystems, significantly influencing eco-hydrological processes. Fragmented patch patterns are common in alpine meadows on the Qinghai-Tibetan Plateau (QTP), potentially leading to the redistribution of water resources by altering material and energy flows. However, there is a paucity of direct observational evidence regarding the impact of fragmented patch patterns on land surface evapotranspiration, and little is known about their effects at the plot scale. Here, we first investigated alpine meadow patch patterns and the corresponding spatial distribution of evapotranspiration through unmanned aerial vehicle (UAV) remote sensing. We then analyzed the role of fragmented patch patterns on alpine meadow evapotranspiration at both patch and plot scales. The results indicated that: 1) The proposed method based on UAV imagery was able to estimate evapotranspiration with satisfactory accuracy (R2 = 0.75, P < 0.001); 2) Evapotranspiration among typical alpine meadow patch types was noticeably different (P < 0.01), with isolated vegetation patches (IV) exhibiting markedly higher values compared to bare soil patches (BP) and original vegetation patches (OV); 3) Most landscape metrics for BP and the patch density index for IV showed positive correlations with evapotranspiration, while the percent of total area and connectivity indices for OV demonstrated negative correlations. Our findings suggest that fragmented patch patterns exacerbate water loss in alpine meadows through excessive evapotranspiration from IV. Restoring vegetation coverage of BP around IV is crucial for the management of degraded alpine meadows.